El sistema de facturación electrónica y su incidencia en el principio de suficiencia recaudatoria llevado a cabo por el servicio de rentas internas en el periodo 2013-2017 - Cuyago Ganán, Vanessa del Pilar (2019)
This research project focuses on the analysis of the Electronic Billing System and its incidence in the Revenue Sufficiency Principle; taking into account, that system was a strategy created by the Servicio de Rentas Internas (S.R.I.), due to the lack of compliance taxpayers, having as result not raising enough funds that allow to support social works, causins tax evasion. The research aim, is to know the incidence of the Revenue Sufficiency Principle based on the Electronic Billing System. By this, tax collections reports of the period 2013-2017 S.R.I. were compared, in the same way, horizontal analysis was elaborated. Subsequently, efficiency indicators were applied in order to know the variations of the amounts raised since the introduction of this system. The methodology applied on this research, is historic method because the revenue reports of the taxes in established periods were compared. And the quantitative method, which was based on a digit numeric analysis was collected from the taxes. At the same time, deductive and descriptive methods were used to establish conclusions about the statistical analysis results to verify the compliance of the Revenue Sufficiency Principle. The results led to conclude that, the implementation of the Electronic Billing System has an acceptable range that facilitates compliance of this constitutional principle, being so, that it shows an increase in the revenue of the taxes (Added Tax Value, Income tax and Special Consumption Tax) according to elapsed time. It was determined that the tax culture of a taxable person is a determining factor to growth of the tax revenue, thus increasins the participation of the General Budget of the State